Sex Differences Regarding the Risk of Incident Venous Thromboembolism in Hospitalized Patients with an Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Pu, Jiaqi; Yi, Qun; Luo, Yuanming; Wei, Hailong; Ge, Huiqing; Liu, Huiguo; Zhang, Jianchu; Li, Xianhua; Pan, Pinhua; Xie, XiuFang; Yi, Mengqiu; Cheng, Lina; et al. (Journal of Atherosclerosis and Thrombosis, 2025)
Aims: Sex differences in the risk of venous thromboembolism (VTE) among patients with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) have so far only been sparsely described. This study aimed to investigate the differences in the risk of VTE events between male and female AECOPD patients and to determine whether any specific risk factors for VTE vary between the sexes.Methods: We prospectively enrolled patients hospitalized for AECOPD from ten medical centers in China. The primary outcome was the occurrence of VTE. Univariate and multivariate logistic regression analyses were conducted to determine whether sex was an independent risk factor for VTE and also to identify any sex-specific risk factors.Results: In total, 13,664 patients were included. VTE occurred in 5.5% of females and 3.3% of males (P＜0.001). A multivariate logistic regression analysis identified female sex as an independent risk factor for VTE in patients with AECOPD (odds ratio [OR] = 1.439, 95% confidence interval [CI] = 1.177–1.759, P＜0.001) after adjusting for confounding factors. Common risk factors for both sexes included age, chronic heart failure, severe lung disease, stroke, a recent surgical history, a history of VTE, and respiratory failure. Additional risk factors unique to males were sepsis (OR = 9.514, 95% CI = 4.513–20.056, P＜0.001), varicose veins (OR = 6.170, 95% CI = 3.237–11.763, P＜0.001), and rheumatological disorders (OR = 2.677, 95% CI = 1.184–6.052, P = 0.018). No sex-specific risk factors were identified for females.Conclusion: Female sex was found to be an independent risk factor for VTE and some sex-specific risk factors exist among inpatients with AECOPD. These findings highlight the importance of considering sex and sex-related factors when assessing the VTE risk in AECOPD patients.